Predicting vehicle belt fit for children ages 6–12. (2nd January 2016) - Reed, Matthew P.; Klinich, Kathleen D.
ABSTRACT: Objective: To predict shoulder belt fit and lap belt fit as a function of child age, vehicle seat characteristics, and belt geometry. Methods: In a previous study, the lap belt and shoulder belt fit of 44 children aged 5–12 were measured in a simulated vehicle seat while varying cushion length, cushion angle, seatback angle, and belt anchorage geometry. A regression model was developed to predict lap belt fit and shoulder belt fit as a function of vehicle parameters and child stature. These regression models were applied to the stature distribution of 6- to 12-year-olds using a range of vehicle geometry data to predict the proportion of children expected to achieve good belt fit in the second-row, outboard seating positions of 46 vehicles when not using belt-positioning boosters. Results: Across the ranges observed in vehicles, lap belt angle had the strongest effect on lap belt fit, although vehicle cushion length also contributed. Shoulder belt fit was most strongly affected by D-ring location. Vehicles with the geometric conditions most suitable for children are estimated to provide good lap belt fit for 25% of children aged 6 to 12. In 20% of vehicles, the shoulder belt is too far inboard for the target child population; 20% of vehicles are estimated to have shoulder belt fit too far outboard for children ages 6 to 12. Conclusions: Based on this geometric analysis, the rear seats of most vehicles are unlikely to provide good lap belt fit for up to 75% of children ages 6–12. Shoulder belt fit is outside the target range for 40% of children. Consequently, children under 12 years of age are likely to experience markedly poorer belt fit when transitioning out of a booster seat.